Инициация флорального морфогенеза у растений различной фотопериодической чувствительности и особенности экспрессии Са2+-зависимой протеинкиназы С - Негрецкий, В.А.; Ковзун, Е.И. (Видавничий дім "Академперіодика" НАН України, 2007)
We study the α-isoform of Ca-dependent protein kinase C (CaPKC) expression during the induction of flowering in the leaves of different photoperiodic sensitive plants. As a result, the expression of Са-dependent proteine kinase С in the leaves of 2 biotypes of tobacco and perilla plants is shown. The 5 long-day induction promoted the CaPKC expression in the leaves of long-day tobacco Nicotiana silvestris L. plants by 143%. A similar activation of the PKC expression was observed after 5 short-day (SD) inductions in SD plants of tobacco M. Mamoth and perilla. This allows us to discuss the Сa-dependent PKC participation in mechanisms of signal transduction during the photoperiodic induction and its involving in the initial stages of floral morphogenesis.